2010
DOI: 10.1086/650369
|View full text |Cite
|
Sign up to set email alerts
|

Speciation Has a Spatial Scale That Depends on Levels of Gene Flow

Abstract: Area is generally assumed to affect speciation rates, but work on the spatial context of speciation has focused mostly on patterns of range overlap between emerging species rather than on questions of geographical scale. A variety of geographical theories of speciation predict that the probability of speciation occurring within a given region should (1) increase with the size of the region and (2) increase as the spatial extent of intraspecific gene flow becomes smaller. Using a survey of speciation events on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
467
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 404 publications
(490 citation statements)
references
References 75 publications
(97 reference statements)
21
467
0
2
Order By: Relevance
“…Accordingly, for example, it appears that 150 species of diving beetle are the product of a single colonisation event followed by speciation within the island of New Guinea (Balke et al 2007), and 1000 species of picture-winged Drosophila are the product of speciation within the Hawaiian archipelago (O'Grady et al 2011). Islands have illustrated that the factors that interact to provide conditions necessary for in situ speciation include isolation (Manceau et al 2010), age (Gillespie & Baldwin 2010) and area (Losos & Schluter 2000;Kisel & Barraclough 2010) of the region concerned, and variables often associated with area, such as topographic complexity and elevation (Whittaker et al 2008). Table 1 Under-explored or in need of revisiting: prospects for using islands to advance understanding in ecology and evolution in general.…”
Section: Evolution Can Play a Key Role In Community Assemblymentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, for example, it appears that 150 species of diving beetle are the product of a single colonisation event followed by speciation within the island of New Guinea (Balke et al 2007), and 1000 species of picture-winged Drosophila are the product of speciation within the Hawaiian archipelago (O'Grady et al 2011). Islands have illustrated that the factors that interact to provide conditions necessary for in situ speciation include isolation (Manceau et al 2010), age (Gillespie & Baldwin 2010) and area (Losos & Schluter 2000;Kisel & Barraclough 2010) of the region concerned, and variables often associated with area, such as topographic complexity and elevation (Whittaker et al 2008). Table 1 Under-explored or in need of revisiting: prospects for using islands to advance understanding in ecology and evolution in general.…”
Section: Evolution Can Play a Key Role In Community Assemblymentioning
confidence: 99%
“…Furthermore, larger areas imply larger population sizes, likely increasing both the number of advantageous mutations and the efficiency with which selection acts upon them (Gavrilets & Losos 2009). Several island-based studies have confirmed the importance of area in cladogenesis (Losos & Schluter 2000;Kisel & Barraclough 2010;Rabosky & Glor 2010). However, beyond Rosindell & Phillimore's (2011) test of their own predictions with island bird data, how the interplay between isolation and area influences the relative importance of anagenesis and cladogenesis largely remains to be evaluated (but see Johnson et al 2000;Valente et al 2014).…”
Section: Community Assemblymentioning
confidence: 99%
See 1 more Smart Citation
“…Because body size correlates with dispersal abilities and thus influences genetic differentiation (Kisel and Barraclough 2010), we tested the effect of species' average body mass.…”
Section: Strength Of the Asynchrony Of Seasons Effect In Relation To mentioning
confidence: 99%
“…It is generally accepted that there is an interplay among dispersal ability, geographic range size, speciation, and extinction that influences a group's evolutionary success (Bilton et al. 2001; Bohonak and Jenkins 2003; Kisel and Barraclough 2010; Sukumaran et al. 2015).…”
mentioning
confidence: 99%